(3OjhGf GHf fHGJI GdeUQjs - (3GdLPGej GdaGQbqj GdeUQj, CHh HcQ, GHf fHGJI, LeGd GdOjf, eMeO Hf eMeO Hf eMeO Hf GdMSf, J (B768(3g`s
(3ChdgG (B:s
(3bGd GdTjN LeGd GdOjf eMeO Hf eMeO Hf fHGJg QMeg Gddg JYGdi jeOM GdfHj Udi Gddg Ydjg hSde(B: (3UMG GdbdH hdG fSeI JJMWQ (B*** (3hdeYI HQb HGdZVG JJSYQs
(3BNQgG (B:s
(3dG BOe GdReGf EP cfJ ajg (B*** (3jG SMGH GdfOi dQRbj cajdG , dj Ojhf Ydi YdGc hgOG (B*** (3hbJ jSQ aCha hGUfY LejdGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 38s
(3eYLe GdeDdajf(B: 3 / 676s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs